2022
DOI: 10.1177/10812865221083323
|View full text |Cite
|
Sign up to set email alerts
|

A slender body theory for the motion of special Cosserat filaments in Stokes flow

Abstract: The motion of filament-like structures in fluid media has been a topic of interest since long. In this regard, a well known slender body theory exists, wherein the fluid flow is assumed to be Stokesian while the filament is modeled as a Kirchhoff rod which can bend and twist but remains inextensible and unshearable. In this work, we relax the inextensibility and unshearability constraints on filaments, i.e., the filament is modeled as a special Cosserat rod. Starting with the boundary integral formulation of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Other approaches to this stiff numerical problem with different treatments of the hydrodynamics have recently been developed. [69][70][71][72][73][74][75][76][77][78] The parameters (Z, D, t f ) = (2, 10 À3 , 10 À2 ), timestep size Dt = 10 À3 , and spatial gridspacing Ds = 1/64 are fixed for the duration unless otherwise stated.…”
Section: Active Kirchhoff Rod Modelmentioning
confidence: 99%
“…Other approaches to this stiff numerical problem with different treatments of the hydrodynamics have recently been developed. [69][70][71][72][73][74][75][76][77][78] The parameters (Z, D, t f ) = (2, 10 À3 , 10 À2 ), timestep size Dt = 10 À3 , and spatial gridspacing Ds = 1/64 are fixed for the duration unless otherwise stated.…”
Section: Active Kirchhoff Rod Modelmentioning
confidence: 99%
“…Recent work has focused on placing these theories back in the context of three-dimensional well-posed partial differential equations (PDEs) (Koens & Lauga 2018; Mori, Ohm & Spirn 2020 a , b ; Mori & Ohm 2021). In particular, it has been shown that SBT can be derived from a three-dimensional boundary integral equation (Koens & Lauga 2018; Garg & Kumar 2022), and that its solution is an approximation to a Stokes PDE with mixed Dirichlet–Neumann boundary data and a boundary condition that the fibre maintain the integrity of its cross-section (Mori et al. 2020 a , b ; Mori & Ohm 2021).…”
Section: Introductionmentioning
confidence: 99%